The mission of the church in Paul's letter to the Philippians in the context of ancient Judaism - Ware, James P. 1957- (Novum Testamentum, Supplements, 2005)
Paul seemingly nowhere in his letters commands his congregations to preach the gospel. Therefore many scholars have concluded that Paul's thinking had little or no place for a mission of the church. This study undertakes a fresh investigation of the question by devoting close attention to a text hitherto overlooked in discussion of early Christian mission, Paul's letter to the Philippians. The Jewish context of Paul's thought in Philippians is the key to unlocking his understanding of church and mission in the letter. The study accordingly begins in Part One with an investigation of conversion of gentiles in ancient Judaism. Part Two, drawing upon this Jewish context, focuses on close exegesis of Philippians, revealing the crucial place of the mission of the church in Paul's thought. The questions addressed by this study go to the heart of our understanding of Paul and of mission in earliest Christianity.